Analisis Faktor Risiko Kematian dengan Penyakit Komorbid Covid-19 - Raden Muhammad Ali Satria; Resty Varia Tutupoho; Djazuly Chalidyanto (Jurnal Keperawatan Silampari, 2020)
This study aimed to analyze comorbid diseases as a risk factor for death due to COVID-19 at Bhakti Dharma Husada Hospital Surabaya. This research method is an observational analytic study with a retrospective study design. The results showed that 358 patients were infected with COVID-19 and confirmed with nose and throat swabs. Sixty-six patients (18%) died from COVID-19. 60.6% were male (OR 1.87, P 0.041), 22.7% aged> 64 years (OR 2.097, P 0.041), and 83.3% of them were co-risk factors. Diabetes mellitus (30.3%) (OR 4,348, P 0,000), and cardiovascular disease (10.6%) (OR 4,319, P 0.016) were the highest risk factors for death in COVID-19. In conclusion, men, old age, diabetes, and hypertension are risk factors for death in COVID-19. Keywords: COVID-19, Diabetes, Hypertension, Comorbid, Elderly, Mortality